Financial risk analysis of Public-Private Partnership (PPP) projects case study on Pandaan - Malang Toll Road - Farid Arif Adi Nugroho; Rosidi Rosidi; Muhammad Tojibussabirin (Interdisciplinary Social Studies, 2024)
This study aims to analyze the financial risks faced by the Pandaan-Malang Toll Road PPP (Public-Private Partnership) project in Indonesia. Data collection techniques include semi-structured in-depth interviews with parties related to the PPP project, including the Directorate General of Infrastructure Financing, the Tolling Road Management Agency (government), and Business Entities (PT Jasamarga Pandaan Malang). The collected data will be analyzed to determine the financial risk factors faced by PPP projects and the financial controls carried out to overcome financial risks in PPP. The results show that the risk of errors in forecasting in the calculation of demand, cost, and revenue projections is a risk that almost often occurs. The Government emphasizes the importance of optimizing the role of PII (Persero) or Indonesia Infrastructure Guarantee Fund (IIGF) as an Infrastructure Guarantee Business Entity (BUPI) to ensure financial sustainability and minimize the impact of sudden shocks on the State Budget due to the provision of Government Guarantees for cooperation projects. This study provides insights or frameworks that can be applied to similar projects, helping to improve risk assessment and decision-making processes in future infrastructure developments.